PROFIL DERMATOFITOSIS DI RUMAH SAKIT UMUM DAERAH DELI SERDANG TAHUN 2015 - 2017 - TAUFIQ .; DIAN ERISYAWANTY BATUBARA (JURNAL ILMIAH MAKSITEK, 2020)
Dermatophytosis is a superficial fungal infection of tissues containing horn substances such as the stratum corneum of theskin, hair and nails. Dermatophytosis infections are caused by dermatophytic fungi. Dermatophytosis is the biggest skinproblem in the world, especially in developing countries. This research objective is to explain the profile of dermatophytosisin Deli Serdang Regional General Hospital in 2015-2017. Penelitian ini merupakan penelitian deskriptif retrospektif.This research method is a retrospective descriptive study. Results: Based on the results of the study, the most cases ofdermatophytosis in 2015-2017 based on the classification according to location are tinea corporis, for female sex more thanmen, for the most variable age cases in 2015 occurred at the age of 45-64 years, 2016- 2017 most at the age of 25-44,based on the most patient in this case is housewife , the common treatment is a combination of systemic anti fungal, topicalanti-fungal and anti-histamine. The most cases of dermatophytosis are tinea corporis, dermatophytosis most commonlyaffects the age of group 45-64, the most genderoften affected by dermatophytosis is women compared to men,dermatophytosis most commonly affects housewives, for the treatment of more dermatophytosis patients treated withcombination therapy (systemic + topical) with anti-histamine.